DETEKSI TEPI UNTUK VALIDASI MODEL TIGA DIMENSI TULANG PANGGUL PADA PERENCANAAN DESAIN IMPLAN - Talitha Asmaria; Rafidah Rahmi; Muhammad Satrio Utomo; Dhyah Annur; Daniel Panghihutan Malau; Muhamad Ikhlasul Amal; Ika Kartika (Widyariset, 2020)
In the process of implant design and fabrication planning, the anatomical background of human bone is an important aspect to determine the accuracy of implant design. To help in understanding the human bone anatomy, replicas of human bone can be reconstructed using three-dimensional (3D) printing technology. This study aims to validate the digital model of human bone and the imaging data of human bone in order to have an appropriate recommendation for designing the total hip replacement (THR). Achieved data from computed tomography scanning (CT-Scan) modality was deciphered to build the digital 3D model human bone. The bone and the digital 3D model of bone were captured to be two-dimensional(2D) data in the same dimension and processed using the algorithm of edge detection. The images from the edge detection process were processed for finding the similarity of the images. The percentage of similarity, precision, and  accuracy between the bone and the digital 3D model have been validated and can be used as a reference in the THR designs.